CHRONIC EFFECTS OF DETERGENT SURFACTANT (LINEAR ALKYLBENZENE SULFONATE I LAS) ON THE GROWTH AND SURVIVAL RATE OF SEA BASS (Lates calcalifor Bloch) LARVAE - Sri Rejeki; Desrina .; Andi Rahmat (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Sea bass (Lates calcal&r Bloch), one of the economically important marine fish, is getting more important for marine-culture. This fish is categorized as a euryhaline species, i.e. with a wide salinity tolerance, range 32 — 35 ppt, and in the river, estuarine and mangrove areas with the salinity between 0 - 25 ppt. The adult of sea bass is spawn in marine waters while the larvae and juvenile are is spawn mostlv found in the estuarine. Estuarine water is known as a good nursery and feeding ground, however it is also knownias a pollutant trap. Therefore, the larvae of seabass and other euryhaline species are very susceptible to this condition.Suryizctant detergent Linear A lkyl—benzene SuU